(untitled) (Fiep Bulletin - online, 2014)
This study aimed at evaluating the interference of physical therapy intervention on the quality of life in mastectomized women or under breast-conserving therapy ones, to compare the result of the quality of life between women who underwent physical therapy (Group I) with those who had not undergone (Group II), as well as between the ones subjected to mastectomy with the ones subjected to breast-conserving therapy, and to identify the profile of the women subjected to of breast cancer surgical treatment. An evaluation form to collect general and specific data and the questionnaire of quality of life SF-36 were used. The results showed that there was a positive interference of the physical therapy treatment in the quality of life of these women. Group I independent from the beginning time and the time that it remained under treatment, showed a significant better quality of life in five of the eight components of questionnaire SF-36, when compared to Group II. It did not have significant difference compared to the quality of life of mastectomized women when compared to breast-conserving therapy. The profile of the women in Group I and Group II were similar, demonstrating the following characteristics: present age and at the date of the surgery between 50 and 79 years, married, elementary degree, white, above normal weight, have not carried hormonal spare therapy, surgical type of mastectomy, without relation with hereditary succession, have not undergone mammary reconstruction, without predominance as to the side of the surgery, right-handed, and in Group I the women remained 5 months in physical therapy treatment on average.